2020
DOI: 10.34172/bi.2020.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bromhexine on clinical outcomes and mortality in COVID-19 patients: A randomized clinical trial

Abstract: Introduction: Bromhexine is a potential therapeutic option in COVID-19, but no data from a randomized clinical trial has been available. The present study aimed to evaluate the efficacy of bromhexine in intensive care unit (ICU) admission, mechanical ventilation, and mortality in patients with COVID-19. Methods: An open-label randomized clinical trial study was performed in Tabriz, North-West of Iran. They were randomized to either the treatment with the bromhexine group or the control group, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 21 publications
2
96
2
4
Order By: Relevance
“…However, in our hands, AMB appears to have a separate and distinct antiviral activity from that of BHX, with BHX being hypothesized 24 and trialed 25 as a repurposed treatment for COVID-19.…”
Section: Discussionmentioning
confidence: 67%
“…However, in our hands, AMB appears to have a separate and distinct antiviral activity from that of BHX, with BHX being hypothesized 24 and trialed 25 as a repurposed treatment for COVID-19.…”
Section: Discussionmentioning
confidence: 67%
“… 25 It has also been included as a potential drug repurposing TMPRSS2 inhibitor and been shown to reduce the ICU admissions, intubation, and mortality rate in patients with COVID19 in a 78 patient open-label, randomized clinical trial. 27 , 40 , 41 Unfortunately, few details of the assay utilized, scale of assay, or its development were described, but the substrate identified in our study as the most amenable for HTS (Boc-Gln-Ala-Arg-AMC) was also used in the Lucas et al study. Notably, we did not detect inhibition of TMPRSS2 from BHH, and confirmed 99.9% purity of our BHH sample ( Supplementary Figure 3 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Irrespective of the role of cell-cell fusion in COVID-19, in light of the observed paradoxical activation of cell-cell fusion by Bromhexine and its lack of inhibitory activity against entry of SARS-CoV-2 spike-pseudotyped lentiviruses on TMPRSS2 expressing cells, we would at the moment caution against clinical use of Bromhexine for treatment or prophylaxis of COVID-19, at least at higher concentrations that aim at the inhibition of TMPRSS2. A recent small randomized trial showed promising results for Bromhexine at 3x 8 mg per day combined with hydroxychloroquine (48), which should result in Bromhexine plasma concentrations in the range of 0.1 µM (49). We are fairly confident to postulate that these favorable results are unlikely due to inhibition of TMPRSS2, although we can’t fully exclude extremely weak activity.…”
Section: Discussionmentioning
confidence: 99%